Dual-Mediation Paths Linking Corporate Social Responsibility to Employee’s Job Performance: A Multilevel Approach - Fang, Miaoying; Fan, Peng; Nepal, Surya; Chang, Po-Chien (Frontiers in Psychology, 2021)
This study attempts to examine the direct impact of CSR initiatives on employee’s job performance, and the indirect relationships between CSR initiatives on employee’s job performance via industrial relations climate and psychological contract fulfillment. Data were from 764 supervisor-subordinate dyads and 271 middle managers which collected from 85 companies. Using a multilevel approach, the results showed that organizational level CSR was positively related to employee’s job performance. Moreover, industrial relations climate and psychological contract fulfillment played mediating effects between CSR initiatives and job performance. This study provides novel theoretical evidence for why and how CSR initiatives improve job performance. Theoretical and practical implications for implementing CSR initiatives are discussed.